PENGEMBANGAN SPK SELEKSI PERANGKAT NAGARI BERBASIS METODE SAW DI DESA KUMANGO UTARA - Rizki, Sestri Novia; Yunaidi, Andri; Nasution, Vani Maharani; Neli, Mery Ulfa; Fitrianto, Adi; Ariawan, Angga (STMIK Sinar Nusantara, 2025)
The selection of village apparatus is an important process in supporting governance at the village level. However, the selection process carried out manually often causes subjectivity and is less efficient. Therefore, a decision support system (DSS) is needed that is able to assist the selection process objectively and in a structured manner. This study aims to develop a DSS for selecting village apparatus based on the Simple Additive Weighting (SAW) method, which is able to provide assessment results based on several relevant criteria. The criteria used in this system include: leadership, discipline, academic achievement, communication skills, ethics and attitudes, and initiative and creativity. The SAW method was chosen because of its ability to calculate the aggregate value of each alternative based on the weight and value of each criterion. This system was developed using the waterfall approach and implemented in the form of a web-based application. The test results show that the system can help simplify the selection process and provide more objective and transparent results. With this DSS, it is hoped that the village apparatus selection process can be carried out more professionally and accountably.